Ford sewing machinists' strikes - commemorative plate, c. 1984 (1984)
1984 1960-2000 "Ford sewing machinists' strikes - commemorative plate, c. 1984" [EP0023], 1984 A ceramic plate, produced by the Transport and General Workers' Union c.1984, to commemorate the 1968 and 1984 strikes for equal pay by sewing machinists at the Ford Motor Company.